Efektivitas Model Pembelajaran Problem Based Learning (PBL) dengan Media Rainbow Card dalam Pembelajaran Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri Model Terpadu Madani Palu - Santosa, Pratama Bayu; Pujiningtyas, Arum; Halifah, Nur (Jurnal Kreatif Online, 2020)
This study describes the effectiveness of the Problem Based Learning (PBL) model with Rainbow card media in learning to write descriptive text for students in 7th graders of SMP Negeri Model Terpadu Madani Palu. This research was a descriptive study. Data in the form of values obtained from students' scores in writing descriptive text were processed and analyzed using the described numbers. The sample was chosen by simple random sampling and the Cerdas Istimewa class with 23 students was picked. Data were collected from descriptive text and the score of a test. The scoring of the written results was in accordance with the assessment criteria for writing descriptions, which were title, identification, description, cover and language use. The results of the average score of students by applying the PBL learning model through the Rainbow Card media in learning to write descriptive texts was 87.8 which were categorized as complete in the Minimum Completeness Criteria (KKM) that has been determined by the school. The percentage value of writing descriptive text achieved was 99.7%. So it was proven that the application of the PBL learning model through the Rainbow Card media in learning to write descriptive text was considered effective.